Body morphology and handgrip strength parameters of the female canoe slalom paddlers - Busta, Jan; Hellebrand, Jaroslav; Kinkorová, Ivana; Duchoňová, Andrea; Hybská, Tereza; Sánchez, Carmen Costa; Vajda, Matej (Frontiers in Physiology, 2024)
Canoe slalom is physically very demanding discipline in which body constitution, body composition and relative strength are significant factors in high performance. While anthropometric and strength parameters are relatively well studied in male athletes, there is a lack of evidence for any conclusions in women. Therefore, the objective of this study was to determine the morphology and upper-limbs strength parameters of female canoe slalom paddlers and to identify if morphological differences exist between performance groups. Altogether 63 female competitors of the 2023 ICF Canoe Slalom World Cup (n = 29) and 2023 ICF Canoe Slalom World Ranking Competition (n = 34) in Prague (Czech Republic) were measured with a battery of anthropometric tests, segmental bioimpedance analysis and hand-grip strength test. The athletes were divided into groups according to age and performance: elite athletes belonging to the world top 10 according to the ICF World Ranking (WORLD, n = 7), international level athletes competing during the World Cup (ELITE, n = 22), international level junior athletes competing in the World Ranking Race (JUNIOR, n = 17) and other lower performance level athletes competing in the World Ranking Race (REST, n = 17). Female slalom paddlers are in general of average body height (~165 cm), lower body mass (~60 kg), BMI (~22 kg/m2) and body fat (~20 %) and without exceptional anthropometric dimensions and proportions. However, differences were detected when performance was factored in. Female paddlers belonging to the world TOP 10 have the largest circumferences of arms and forearms, their somatotype is more mesomorphic with a lower proportion of total body fat and higher proportion of muscle mass. In addition, the WORLD group differs significantly in upper limb strength. This shows the significance of muscular strength and power for canoe slalom athletes and the importance of well-developed musculature in operating the boat in the unstable environment. Being a successful female canoe slalom athlete requires a well-developed musculature, maximizing strength capabilities while maintaining a low body weight through limited hypertrophy of the lower limbs, maintaining a low level of body fat.